The effects of spraying power on microstructure, magnetic and dielectric properties of plasma sprayed cobalt ferrite coatings - Yuanbao Miao; Huanyu Zhu; Pengfei Gao; Liangfeng Li (Journal of Materials Research and Technology, 2020)
In this work, the effects of spraying power on the microstructure, orientation, magnetic and dielectric properties of plasma sprayed cobalt ferrite coatings were investigated. With the increase of spraying power, the compactness of the coatings was increased, and the orientation degree of <100> was also increased. However, the thickness and dielectric constant of the coatings were increased first and then decreased. The melting degree, which was induced by spraying powers, was the key factor to affect the microstructure and properties of the coatings.